مدى فعالية دور التكلفة المستهدفة في زيادة القدرة التنافسية لخدمات البنوك : دراسة تحليلية - غنيمي، سامي محمد أحمد (جامعة الزقازيق - كلية التجارة, 2014)
تناول الباحث في هذه الدراسة مدي فعالية تطبيق أسلوب التكلفة المستهدفة في خفض تكاليف خدمات قطاع البنوك التجارية لدعم القدرة التنافسية، مع الحفاظ على جودة تلك الخدمات وتحسينها لمواجهة المنافسة السائدة في هذا القطاع، وتوفير المقومات اللازمة للتطبيق، إلى جانب التعرف على التعرف على المشكلات والصعوبات التي قد تواجه عملية تطبيق أسلوب التكلفة المستهدفة وإمكانية وضع الحلول المناسبة للتغلب عليها، لتوفير المزايا التي يحققها هذا الأسلوب في تسعير الخدمات بالبنوك التجارية. وسعى الباحث من وراء هذه الدراسة إلى تحقيق هدفا رئيسيا ألا وهو محاولة التعرف على مدي إمكانية وفعالية استخدام أسلوب التكلفة المستهدفة في مجال خفض التكلفة وتسعير الخدمات في البنوك التجارية، حيث حقق هذا الأسلوب نتائج إيجابية في الإنتاج بالشركات الصناعية، وتوصل في النهاية إلى أنة بالرغم من الصعوبات التى قد تواجه التطبيق في قطاع الخدمات المصرفية، إلا أن تطبيق أسلوب التكلفة المستهدفة يساعد على دعم القدرة التنافسية لخدمات البنوك التجارية ويدعم تحقيق الأهداف الإستراتيجية للبنك وهو البقاء والنمو والاستمرار في سوق المنافسة السائدة في الوقت الحاضر، حيث أسفرت الدراسة عن عدة نتائج وتوصيات كان من أهمها ما يلي:- (1) تفعيل دور نظم محاسبة التكاليف في البنوك، وتوفير الكفاءات العلمية والعملية القادرة على تطبيق أساليب الإدارة الإستراتيجية لخفض التكلفة وتسعير الخدمات المصرفية. (2) تطبيق أسلوب التكلفة المستهدفة في تسعير الخدمات المصرفية بدلاً من الأساليب التقليدية، نظراً لما يحققه ذلك من مزايا للبنوك وزيادة قدرتها على المنافسة. Eating researcher in this study the effectiveness of the application of cost method targeted at reducing the cost of services for the commercial banking sector to support competitiveness, while maintaining the quality of those services and improved to meet the competition prevailing in this sector, and to provide the necessary ingredients for the application in addition to recognition to identify the problems and difficulties that may face the process of applying the target cost method and the possibility of developing appropriate solutions to overcome them, to provide the benefits achieved by this method in the pricing of services to commercial banks. And sought the researcher behind the study to achieve a major goal, namely trying to identify the extent feasibility and effectiveness of the use of cost method target in reducing the cost and pricing of services in commercial banks, where he achieved this method positive results in the production companies, industrial and concluded in the end that despite difficulties that may face the application in the banking sector, but that the application of cost method target helps to support the competitiveness of the services of commercial banks and supports the strategic objectives of the Bank is to survive and grow and continue to market competition prevailing at the present time, where The study of several findings and recommendations was including the following:- activating the role of cost accounting systems in banks, and the (1) provision of scientific and practical competencies capable of applying strategic management methods to reduce the cost and pricing of banking services. (2) applying a target cost in the pricing of banking services rather than traditional methods, owing to achieve the advantages to banks and increase their competitiveness.
753899
Keywords: الخدمات المصرفية -- محاسبة التكاليف -- جودة الخدمات -- المنافسة الإقتصادية -- البنوك التجارية